Promoter-Like Mutant with Increased Expression of the Glycerol Kinase Operon of Escherichia coli - Berman-Kurtz, Myra (1971)
A glycerol-specific phenotypic revertant isolated from a mutant of Escherichia coli missing enzyme I of the phosphoenolpyruvate phosphotransferase system was studied. This revertant is capable of producing higher levels of glycerol kinase and the protein mediating the facilitated diffusion of glycerol (facilitator) than wild-type cells. The kinase of the revertant is indistinguishable from the wild-type enzyme with respect to its sensitivity to feedback inhibition by fructose-1,6-diphosphate, its pH optimum, and its turnover number. The synthesis of glycerol kinase in strains bearing the suppressor locus is resistant to catabolite repression. The suppressor mutation mapped at the known glpK locus. Thus, it is suggested that the mutation occurred in the promoter of the operon specifying the kinase and the facilitator.